PROBLEMATIKA IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 7 TAHUN 2019 TENTANG PELAYANAN ADMINISTRASI KEPENDUDUKAN SECARA DARING DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GROBOGAN - Adila Almas Hasna Asyari; Anjar Sri Ciptorukmi Nugraheni (Sekolah Tinggi Pariwisata Mataram, 2021)
Grobogan Districts. The purpose of this research was to analys the implementation of the Minister of Home Affairs Regulation Number 7 year 2019 concerning Online Population Administration Services by the Department of Population and Civil Registration of Grobogan Districts, and to analys the problems that occur in the implementation of this online population administration service. The type of this research is qualitative using a descriptive approach. Informants in this research were official and community employees who the authors took based on purposive sampling technique. The primary data were obtained through interviews and observations to the users of the simple tenant application, and service innovation staff of staff service innovations at the Dispendukcapil of Grobogan, secondary data obtained through library research and document studies. This research uses a qualitative descriptive technique by observing the process, activity and development of the object under study off simpel tenan application. From the results of the research and discussion in this study, conclusions were made regarding the implementation carried out by the Dispendukcapil of Grobogan, applied by creating a bold service application, by simpel tenan application that was in accordance with the Regulation of the Minister of Home Affairs Number 7 of 2019 concerning Online Population Administration Services. The problem with the brave service was identified by the author by using 5 (five) factors as an indicator of legal effectiveness. Problems with legal factors do not exist, problems with law enforcement factors, is not providing socialization to the public about simpel tenan applications, problems with facilities and facilities, which require more adequate servers and networks, on community factors, namely people are less active in adding insight about innovative products. regional and cultural factors, no problems were found.